2021
DOI: 10.3390/su132011130
|View full text |Cite
|
Sign up to set email alerts
|

Green Brand Equity—Empirical Experience from a Systematic Literature Review

Abstract: Our study aims to analyze factors determining the green brand equity (GBE) based on a systematic literature review (SLR) according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) statement. We posed 3 research questions and searched five databases (Scopus, Web of Sciences, Google Scholar, EBSCO, and Elsevier) for studies containing the term ‘green brand equity’ and the combination of two terms: ‘brand equity’ and ‘green’. Additionally, the backward and forward snowballing met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 122 publications
(296 reference statements)
0
8
0
Order By: Relevance
“…Thus, GBE is a recent trend gaining attention among researchers and practitioners. In addition, researchers have found that GBE can positively affect consumers in many other ways, such as positive word of mouth (Bekk et al , 2016), brand attitude (Khandelwal et al , 2019; Bekk et al , 2016) and intention to buy (Górska-Warsewicz et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, GBE is a recent trend gaining attention among researchers and practitioners. In addition, researchers have found that GBE can positively affect consumers in many other ways, such as positive word of mouth (Bekk et al , 2016), brand attitude (Khandelwal et al , 2019; Bekk et al , 2016) and intention to buy (Górska-Warsewicz et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…We performed a literature search based on the PRISMA guidelines [48,49], which are widely applied in many academic studies [50][51][52][53]. Our search focused on studies published until 15 January 2021 in the Scopus and Web of Science databases.…”
Section: Methodsmentioning
confidence: 99%
“…The SLR was conducted using the Preferred Reporting Items for Systematic Literature Reviews and the Meta-Analyses (PRISMA) method [ 82 , 83 ]. This research method was chosen because of its importance in many academic studies [ 65 , 67 , 68 , 84 , 85 , 86 ].…”
Section: Methodsmentioning
confidence: 99%
“…Based on the above analysis and previous research [ 65 , 67 , 68 ], it was assumed that the traditional elements that make up BE are brand loyalty, perceived quality, brand associations, and brand awareness from D.A.’s concept [ 30 ] and brand knowledge, brand awareness, and brand image from K.L. Keller’s concept [ 31 ].…”
Section: Literature Reviewmentioning
confidence: 99%